Assessment of Indian Open Access Social Science Publications through the Application of Growth Models - Karadia, Alekha; Sahoo, Jyotshna; Mohanty, Basudev (DESIDOC Journal of Library & Information Technology, 2025)
The study aims to investigate and report on the growth of Open-Access (OA) social science scholarly publications in India from 2013 to 2022 by applying various growth models. During the study period, 13,378 records were extracted from the scopus database, and a dataset was created to enhance the effectiveness of statistical analysis using the “R” Open-Source software. It is found that the Exponential Growth Model, with a peak R-squared value of 0.9749, highlights a substantial Annual Growth Rate (AGR), reaching its highest in 2020 (94.43 %) and lowest in 2021 (7.14 %). The Mean Relative Growth Rate (0.42) signifies the average growth pace, and doubling time (average 1.81) indicates a notably rapid doubling rate in OA social science publications. India ranks 18th in open-access social science publications with 13,378 papers (1.31 %), reflecting a modest contribution compared to China (5.12 %) and Germany (3.78 %). A cross-disciplinary analysis highlights significant disparities, with medicine leading at 115,228 publications (17.67 %), while social sciences (2.05 %) and humanities contribute comparatively less (0.39 %). This emphasises the urgent need for substantial support from Indian social scientists to augment the OA movement in the field. Notably, 2021 witnessed a rise to 2.92 citations annually, contrasting sharply with 2022’s decline to 1.65, revealing dynamic trends in influence within Indian open-access social science papers.